An analytical approach in accounting for social values of ecosystem services in a Ramsar site: A case study in the Mekong Delta, Vietnam / Ho Huu Loc, Nguyen Thi Hong Diep, Vo Thanh Tuan, Yoshihisa Shimizu - Ho, Huu Loc
Within the existing literature body, the evaluation exercises predominantly adopt expert disciplined assessments to explore the biophysical conditions and economic values of ecosystem services (ES) and ecosystem disservices (EDS). This preference largely emerges from the relative convenience in data collection and quantification of these approaches, collectively accrue to practitioners’ beliefs that unless explicitly quantified and monetized, these benefits will be negligible. Social aspects of ecosystems contributions to human well-being, on the other hand, are comparatively harder to grasp, thus predominantly overlooked in the general assessment of ES and EDS. To alleviate this imbalance, we presented a case study in exploring relevant ES and EDS within the context of a protected area using non-monetary methods with the aid of the local community. In particular, through deliberative mapping approach, the manuscript strived to locate, quantify, and assess a full range of relevant ES and EDS as perceived by local inhabitants across the landscape of U Minh Thuong National Park (UMTNP), Vietnam. Within the scope of this paper, we also delved into how socio-cultural perceptions and preferences towards these natural resources diverge among groups of respondents. Through the presented research, we strived to consolidate the baseline understanding regarding the ES profile of the research area with relevant social insights, paving the way for the design and implementation of sustainable management strategies. Finally, this manuscript also sought to present a practical measure to account for social dimensions and their relevance to the general assessment of ES.